The concept of Gustav Radbrukhʼs natural law - Podkovenko, Tetiana (Actual problems of law (Aktual'ni problemi pravoznavstva), 2021)
The article deals with the reasons for the revival of the concept of natural law in Western Europe, especially in Germany, after the collapse of the National Socialist regime. G. Radbruch’s views on law and principles of law are highlighted.Gustav Radbruch is a representative of the neo-Kantian philosophy of law, the basic idea of which is the statement that law is a product of human spiritual activity. Neo-Kantians recognized the connection between law and axiology. The philosophical and legal axiom of neo-Kantianism is the position that the basis of legal values is formed by the person with whom the basic legal values are connected: freedom, equality, interest and others. Definitions of law were built on these fundamental concepts.The focus is on the «Radbruch formula» as an approach to resolving the conflict between legal stability and justice – elements of the scientist’s theory of the «idea of law», which also includes the expediency.The idea of justice, expressed in the famous «Radbruch formula», contributed to the postwar renaissance of the concept of natural law not only in Germany, but became fundamental to all Western European legal thought. In the work «Legal law and illegal law» G. Radbruch uses the neo-Kantian concept of justice as a meaningful element of the idea of law and the essence of the concept of law. Justice itself, its meaning is revealed through the principle of equality; this principle, according to G. Radbruch, is absent in positive legal law, which is a «legal wrong». Reasonable guidelines for legal relations, such as justice and equality, lie in the transcendental understanding of law.Justice, expediency and legal certainty as legal values are interrelated components of the idea of law, which at the same time can be in a contradictory relationship, conflict, antinomy. Later, G. Radbruch concretized the approach to solving the antinomy of the idea of law – in favor of the priority of justice over legitimacy and expediency.Gustav Radbruch’s philosophical and legal ideas continue to be modern and relevant, teach to think and understand law more deeply. Lawyers’ awareness of the main leitmotif – the law must serve justice – will help strengthen confidence in national law. Gustav Radbruch is an outstanding theorist of law, who considered the principle of legal certainty, justice and politics as three fundamental principles of law. Today, the principle of legal certainty is recognized at the international level as one of the main requirements for ensuring the rule of law. G. Radbruch’s formula, according to which a positive law must be declared illegal and its provisions must not be complied with if this law: firstly, clearly and blatantly contradicts the principle of social justice and secondly, destroys the formal equality established by natural law individuals and organizations, and today remains relevant.